the Pengaruh Lingkungan Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai - Sylvia Margareth Sabarofek (Cakrawala Management Business Journal, 2022)
This research aims to test and analyze the influence of the work environment and work motivation on employee performance in the BAPPEDA Manokwari Office. The population in this study was all bappeda office employees who numbered 25 people and all were respondents. This type of research uses quantitative research. Research data collection methods used by questionnaires and interviews. Multiple linear regression is the analysis of the data used. The results stated that the work environment and work motivation simultaneously have a positive and significant effect on performance, the work environment has a significant effect on the performance of BAPPEDA employees, work motivation has a significant effect on the performance of BAPPEDA employees. Keywords: Work Environment, Motivation, Employee Performance.